CHANGES IN SHEEP TRANSHUMANCE IN ROMANIA. A CASE-STUDY FROM MĂRGINIMEA SIBIULUI – SOUTHERN CARPATHIANS - SHIGERU SHIRASAKA; KAZUKO URUSHIBARA–YOSHINO (Revue Roumaine de Géographie)
During the communist regime, cooperative sheep farms accounted for about half the total number of sheep in Romania. Individual sheep transhumance was allowed in poorly productive areas. One of the main sheep transhumance areas was located on the northern slope of the Cindrel Mountains in the South Carpathian Mountains. The traditional transhumance style in this area was “intermediate-stationed transhumance”. During the former regime, the sheep holders were required to inform the government every year of their sheep numbers and increases from the previous year. The real numbers were very hard to obtain statistically or through questionnaires. Land degradation, which was very obvious, can be estimated from the geo-ecological conditions. All of the sheep flocks moved from the mother village (Jina) to the summer range (top of mountains), and the winter range in the Banat Plain or in the Danube Delta. After the revolution in 1989, individual sheep holders continued to operate in the same fashion. It is possible, though, to infer that the number of sheep taken to the mountains top for summer pasturing became smaller. The winter range in the Banat Plain is about 300 km from the mother village. Gradually, shepherds came to use trucks or freight trains to transfer their flocks this distance. After the country’s EU ascension in 2007, the flock units in the Banat Plain became bigger, reaching 1,000 or 1,500 heads. Some of the sheep remained in the Banat Plain throughout the year. The other flocks were moved up in the mountain in summer at about 1800 m a.s.l. Only 10% of all sheep registered in Jina were move to the mountains top. Thus, in the future, intermediate-stationed transhumance will gradually disappear. In its place, transhumance in the lowlands will increase as sheep numbers keep growing. However, if the sheep holders require higher quality cheese and sheep meat in the future, it will be necessary to take the sheeps to the mountain top in summer.